DAMPAK PERUBAHAN KOMUNIKASI INTERNAL DI INDUSTRI PERHOTELAN DI KOTA BANDUNG SELAMA MASA PANDEMI - Era Purike; Priatna Kesumah (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
The hospitality industry is one of the industries that has been hit hard during the pandemic. According to the chairman of the Indonesian Hotel and Restaurant Association (PHRI) during the pandemic, 62 hotels were sold in Bandung. Due to the decline in hotel occupancy rates during the pandemic due to large-scale restrictions. The hotel industry that survives is also required to implement strict health protocols which have an impact on reducing face-to-face interactions between hotel employees. The research was conducted through a limited survey. Researchers also observe and interview in which respondents answered questions that had been prepared by the researcher. The results showed that the majority of respondents answered that information system changes made by minimizing physical or face-to-face contact had caused misunderstandings in carrying out agreed tasks in online forums such as WhatsApp and other online communication features such as Zoom and Google Meet. The impacts that respondents complain about are communicators who misplace themselves in situations faced by other people, multiple interpretations messages, misunderstood messages, individuals less respect and not ready to listen to work-related complaints. It causes mistakes made by workers in the hotel industry which have an impact on the services provided to customers.